Can intensive phonomotor therapy modify accent? A phase I study. (December 2015) - Oelke, Megan; Sachet, Lauril; Nagle, Kathy; Bislick, Lauren; Brookshire, C. Elizabeth; Kendall, Diane L.
Abstract : A variety of accent modification approaches exist for non-native English speakers. The training program developed for this study, phonomotor treatment, is based on a parallel distributed processing model of phonology and was hypothesized to modify accent via improved sound production in a non-native English speaker. The participant was a 20-year-old native Wuhan and Mandarin Chinese speaker. In the context of a single-subject repeated probe design, he received probes prior to, during, and immediately following training. Training was intensive and delivered for 20 hours over 2 weeks. Post-training results revealed statistically significant improvements in trained phoneme production in isolation and reduced listener effort at the sentence level. Generalization results were limited, suggesting that future participants may benefit from an increased training period and additional program development. Data gathered from this study may also help to inform the development of subsequent trials of the same program.